Mobbing among nurses: the defensive role of group identification and organizational identification. - Topa, Gabriela; Moriano, Juan Antonio; Morales, José Francisco (Anales de Psicología / Annals of Psychology, 2009)
The aim of this paper is twofold. First, to examine the relation-ships between organizational identification and group identification with work harassment. Second, to analyze the mediator role of perceived social support from different sources- organizational and group- into the identi-fication and harassment relationships. Using a sample of 388 Spanish nurses we found partial support for our hypotheses. Structural Equation modeling analyses showed that organizational identification and group identification were negative predictors of harassment behaviors. More-over, results proved that perceived group support partially mediated the group identification-harassment relation. At the same time, perceived organizational support failed to mediate the organizational identification- harassment relation. These results validated and expanded the previous research on organizational identification and work related behaviors.